Representasi Standar Kecantikan Dalam Film “The Ugly Step Sister” - Raihan Zaidan; Alina Ruskamila (CV. ITTC INDONESIA, 2025)
This study aims to analyze the construction of beauty standards in the film The Ugly Stepsister released in 2025 and how these standards influence the identity formation of the main character. The research is based on the view that media plays an important role in shaping social perceptions of beauty. The film illustrates the pressure experienced by women to conform to the ideal physical appearance valued in Norwegian society. The method used is Roland Barthes’ semiotics from 1976 which consists of the stages of denotation, connotation and myth, with data collected through direct observation of several key scenes in the film. The findings show that Elvira’s actions such as removing her braces, undergoing nose surgery, engaging in extreme weight loss practices and applying eyelash extensions represent efforts to meet culturally institutionalized beauty standards. Using Stuart Hall’s representation theory from 1997 the study finds that the film not only presents reality but also constructs beauty as something that must be achieved through physical modification. The study concludes that The Ugly Stepsister demonstrates the strong social pressure placed on women to fulfill certain beauty expectations. Therefore critical awareness is needed in understanding media constructions so that women do not become trapped in oppressive aesthetic demands.